2021
DOI: 10.1007/s12325-021-01753-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Patients with Hepatitis C Virus Treated with Glecaprevir/Pibrentasvir from Clinical Trials and Real-World Cohorts

Abstract: Introduction More than 70 million people are estimated to be infected with hepatitis C virus (HCV) globally. If left untreated, HCV infection can lead to complications such as extensive liver fibrosis, cirrhosis, and hepatocellular carcinoma (HCC). Evolution of treatments has resulted in highly effective and well-tolerated all-oral direct-acting antivirals. The pangenotypic regimen of glecaprevir/pibrentasvir is approved for treating HCV for patients without cirrhosis or with compensated cirrhosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The data in this paper build on those in large real-world cohorts across wide ranging populations covering those with cirrhosis, pediatric patients, and those with GT3 infection, further demonstrating the breadth of applicability for the regimen without compromising safety/efficacy [ 11 , 20 25 ]. In this analysis, the proportion of patients with clinical evidence suggestive of PHT at baseline was similar between groups treated with 8 and 12 weeks of G/P, suggesting that the patient population in EXPEDITION-8 was similar to those in previous clinical trials of 12-week G/P.…”
Section: Discussionmentioning
confidence: 97%
“…The data in this paper build on those in large real-world cohorts across wide ranging populations covering those with cirrhosis, pediatric patients, and those with GT3 infection, further demonstrating the breadth of applicability for the regimen without compromising safety/efficacy [ 11 , 20 25 ]. In this analysis, the proportion of patients with clinical evidence suggestive of PHT at baseline was similar between groups treated with 8 and 12 weeks of G/P, suggesting that the patient population in EXPEDITION-8 was similar to those in previous clinical trials of 12-week G/P.…”
Section: Discussionmentioning
confidence: 97%
“…These results were in accordance with previous study which also found that SVR obtained by DAAs therapy was correlated to improved OS and PFS in HCV-related HCC patients. 36,37 The safety and efficiency of DAAs therapy has been confirmed by various studies, 38 as it has the advantage of shorter treatment duration, better response rates, and milder side effects. 33,39 Recently, the arrival of IFN-free DAAs has not only revolutionized the treatment of HCV infection, but also impacted the epidemiological landscape for HCV-related HCC.…”
Section: Discussionmentioning
confidence: 91%
“…The safety and efficiency of DAAs therapy has been confirmed by various studies, 38 as it has the advantage of shorter treatment duration, better response rates, and milder side effects 33,39 . Recently, the arrival of IFN‐free DAAs has not only revolutionized the treatment of HCV infection, but also impacted the epidemiological landscape for HCV‐related HCC.…”
Section: Discussionmentioning
confidence: 98%
“…A post hoc analysis of G/P in patients in clinical trials and real-world studies found that it was well tolerated in different populations of patients. 8 However other DAAs, such as sofosbuvir/ledipasvir, have shown higher relapse rates for 8 week treatment compared with 12 week treatment among PLWH. 9 Also, the higher proportion of active drug users among coinfected HIV/HCV patients compared with HCV-monoinfected patients could result in reduced sustained viral response (SVR) rates.…”
Section: Introductionmentioning
confidence: 99%